Juvenile Neuromuscular Systems Show Amplified Disturbance to Muscle Unloading - Deschenes, Michael R.; Patek, Leah G.; Trebelhorn, Audrey M.; High, Madeline C.; Flannery, Rachel E. (Frontiers in Physiology, 2021)
Muscle unloading results in severe disturbance in neuromuscular function. During juvenile stages of natural development, the neuromuscular system experiences a high degree of plasticity in function and structure. This study aimed to determine whether muscle unloading imposed during juvenile development would elicit more severe disruption in neuromuscular function than when imposed on fully developed, mature neuromuscular systems. Twenty juvenile (3 months old) and 20 mature (8 months old) rats were equally divided into unloaded and control groups yielding a total of 4 groups (N=10/each). Following the 2 week intervention period, soleus muscles were surgically extracted and using an ex vivo muscle stimulation and recording system, were examined for neuromuscular function. The unloading protocol was found to have elicited significant (P ≤ 0.05) declines in whole muscle wet weight in both juvenile and mature muscles, but of a similar degree (P=0.286). Results also showed that juvenile muscles displayed significantly greater decay in peak force due to unloading than mature muscles, such a finding was also made for specific tension or force/muscle mass. When examining neuromuscular efficiency, i.e. function of the neuromuscular junction, it again was noted that juvenile systems were more negatively affected by muscle unloading than mature systems. These results indicate that juvenile neuromuscular systems are more sensitive to the effects of unloading than mature ones, and that the primary locus of this developmental related difference is likely the neuromuscular junction.